Study of Mannheim peritonitis index for predicting morbidity and mortality in patients of hollow viscous perforation: In a tertiary care hospital of Eastern India - Parikshita Dalai; Akshay Chawla; Sumit Ranjan Samal; Swapnarani Behera; Dharma Niranjan Mishra (Asian Journal of Medical Sciences, 2023)
Background: Peritonitis is the inflammation of peritoneum, the serosal membrane that lines the abdominal cavity and organs inside. The hollow viscous perforation (HVP) is one of the most common surgical emergencies encountered by surgeons on a daily basis. Mannheim Peritonitis Index (MPI) is a simple and effective method in predicting the morbidity of patients with HVP. Aims and Objectives: This study attempts to evaluate the prognostic value of MPI scoring system in patients with peritonitis due to HVP. Materials and Methods: This is a clinical, prospective, and observational study. There were 50 patients with HVP (stomach, duodenum, ileum, and appendix) admitted in Srirama Chandra Bhanja Medical College and Hospital from March 2021 to October 2022 included in the study. Necessary data were collected; MPI score was calculated for each patient and analyzed. Results: The number of post-operative complications, duration of intensive care unit, and hospital stay proportionately increased with the MPI score. Out of the eight variables used in this scoring system, duration of pain, intraperitoneal fluid and organ failure on admission carried more significance in predicting the morbidity in the post-operative period than the other variables. Conclusion: MPI is a simple and effective method in predicting the morbidity of patients with HVP and to assess it as a clinical tool in stratifying these patients according to individual surgical risk.